Bioinspired copper single‐atom nanozyme as a superoxide dismutase‐like antioxidant for sepsis treatment. Issue 4 (13th July 2022) - Yang, Ji; Zhang, Ruofei; Zhao, Hanqing; Qi, Haifeng; Li, Jingyun; Li, Jian‐Feng; Zhou, Xinyao; Wang, Aiqin; Fan, Kelong; Yan, Xiyun; Zhang, Tao
Abstract: Sepsis is a systemic inflammatory response syndrome with high morbidity and mortality mediated by infection‐caused oxidative stress. Early antioxidant intervention by removing excessively produced reactive oxygen and nitrogen species (RONS) is beneficial to the prevention and treatment of sepsis. However, traditional antioxidants have failed to improve patient outcomes due to insufficient activity and sustainability. Herein, by mimicking the electronic and structural characteristics of natural Cu‐only superoxide dismutase (SOD5), a single‐atom nanozyme (SAzyme) featuring coordinately unsaturated and atomically dispersed Cu‐N4 site was synthesized for effective sepsis treatment. The de novo‐designed Cu‐SAzyme exhibits a superior SOD‐like activity to efficiently eliminate O2 −, which is the source of multiple RONS, thus blocking the free radical chain reaction and subsequent inflammatory response in the early stage of sepsis. Moreover, the Cu‐SAzyme effectively harnessed systemic inflammation and multi‐organ injuries in sepsis animal models. These findings indicate that the developed Cu‐SAzyme possesses great potential as therapeutic nanomedicines for the treatment of sepsis. Abstract : A SOD‐inspired copper single‐atom nanozyme (Cu‐SAzyme) was designed and synthesized by a two‐step scaffold‐adsorption method. The Cu‐SAzyme exhibits high catalytic activity to scavenge superoxide anion, the initiator of ROS, and thus effectively prevents the disease progression in septic animals.